DUKUNGAN SOSIAL DAN KETAHANAN KELUARGA PESERTA DAN BUKAN PESERTA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI - Herawati, Tin; Krisnatuti, Diah; Rukmayanti, Ina Yanuar (Jurnal Ilmu Keluarga dan Konsumen, 2012)
This study generally aims to assess social support for family strength in Sadeng Kolot Village, Leuwisadeng district, Bogor. The study involved 70 families, consist of 35 PNPM families who were selected randomly and 35 nonPNPM families who were selected by Snowball method. Data were analyzed using descriptive test, independent samples t-test, Pearson correlation test ,and multiple linear regression test. PNPM families accepted social support from neighbors. PNPM and nonPNPM families had low morbidity rate and also high social strength and psychosocial strength. The research found out the significant difference of social support and family strength between PNPM and nonPNPM families. Social support from neighbors, family, and nuclear families correlated significantly with total family strength. Family strength were affected by PNPM Mandiri membership status, income per capita per month, and the amount of assets.